Oxidation and ablation behaviours of a SiCnw@SiC–Si coating fabricated for carbon-fibre-reinforced carbon-matrix composites via thermal evaporation and gaseous silicon infiltration. Issue 6 (15th March 2023) - Xie, Xiangmin; Tang, Xian; Su, Zhe'an; Liao, Jingjing; Yang, Cheng; Huang, Qizhong
Abstract: A SiC-nanowire-modified SiC–Si (SiCnw @SiC–Si) coating was prepared for carbon-fibre-reinforced carbon-matrix (C/C) composites using a two-step method based on thermal evaporation and gaseous silicon infiltration, and the effects of SiC nanowires on the oxidation and ablation behaviours of the coated samples were studied. Oxidation tests conducted at 1500 °C revealed that the weight loss of the SiC–Si-coated C/C composite was 15.85% after 6 h, whereas the SiCnw @SiC–Si-coated C/C composite experienced a significantly lower weight loss of 1.27% after 50 h. Ablation tests suggested that the mass and linear ablation rates of the SiCnw @SiC–Si-coated C/C composite were 0.05 mg/s and 0.09 μm/s, respectively; they were reduced by 78.26 and 92.74%, respectively, compared with those of the SiC–Si-coated C/C composite. Careful characterisation suggested that the network structure of the SiC nanowires in the SiC–Si phase can suppress crack propagation and firmly attach to the coating surface to enhance the interfacial adhesion between the coating and substrate, leading to improved anti-oxidation and anti-ablation properties. The SiCnw @SiC–Si coating could offer a technological foundation for preventing the oxidation and ablation of C/C composites in aerospace engineering.